SUKUK NEGARA DAN PEMBANGUNAN INFRASTRUKTUR DI INDONESIA - Anisa Ilmia (Finansha: Journal of Sharia Financial Management, 2020)
The economic growth of a country is strongly influenced by the availability of infrastructure that will support various economic activities. The need for the availability of funds and infrastructure development is a dilemma given the limited sources of state budget revenue. The issuance of Sovereign Sukuk (SBSN) is one of the government’s breakthrough to overcome this problem and is expected to be a solution option that can be used for infrastructure financing. This study aims to identify the development and contribution of Sovereign Sukuk (SBSN) for infrastructure development in Indonesia, include during the Covid-19 pandemic. From the results of data analysis using the library research method, its known that Sovereign Sukuk have a role as a source of APBN financing. The issuance of Sovereign Sukuk with various series of sukuk has contributed greatly to the develpoment of the various infrastructure projects in Indonesia. The total value of issuance and outstanding of Sovereign Sukuk also tends to increase every year which shows that Sovereign Sukuk is a financial instrument that is in demand by investors, both institutional investors and retail/individual investors because apart from being able to nvest, investors can also contribute to the country’s development.